2012
DOI: 10.1007/s00442-012-2309-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedbacks to growth of an invasive grass through alteration of nitrogen cycling

Abstract: Understanding the mechanisms by which invasive plants maintain dominance is essential to achieving long-term restoration goals. While many reports have suggested invasive plants alter resource availability, experimental tests of feedbacks between invasive plants and soil resources are lacking. We used field observations and experimental manipulations to test if the invasive grass Microstegium vimineum both causes and benefits from altered soil nitrogen (N) cycling. To quantify M. vimineum effects on N dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 39 publications
4
83
0
Order By: Relevance
“…Tree species can have a strong influence on soil properties [22]. Different vegetation types can have varying influence on the rate of soil N and P input, and these can affect the soil nutrient accumulation and loss [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Tree species can have a strong influence on soil properties [22]. Different vegetation types can have varying influence on the rate of soil N and P input, and these can affect the soil nutrient accumulation and loss [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Estes Park, CO, USA Fig. 1c,3c (7,8) v www.esajournals.org Hocking (1947);12, Mack (2003);13, Mitich (1992); 14, Miklovic and Galatowitsch (2005); 15, Murrell et al (2011);16, Bailey and Wisskirchen (2006);17, Norton et al (2008);18, Ortega et al (2012);19, Duncan et al (2001);20, Price et al (2011);21, Valley and Newman (1998);22, Verlinden et al (2013);23, Abraham et al (2009);24, Bennett et al (2011);25, Firn et al (2010);26, Flory and Clay (2010); 27, Kolb and Alpert (2003); 28, Lee et al (2012); 29, Lopez-Rosas and Moreno-Casasola (2012);30, Nernberg and Dale (1997);31, O'Dwyer and Attiwill (1999); 32, Orloff et al (2013);33, Menalled et al (2008); 34, Parkinson et al (2013); 35, Thomsen et al (2006);36, Veblen and Young (2009).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The results of studies on the leaves of this plant have shown that F. alnus leaf litter has the capacity to alter soil properties and microbial function by stimulating N mineralization [12]- [16]. Bark of Frangula alnus Mill also referred as Frangulae cortex is widely used as laxative and can be found as component of herbal laxative preparations Laxative property of F. alnus bark has been attributed to the presence of anthraquinone glycoside derivatives, glucofrangulins and frangulins [17].…”
Section: Introductionmentioning
confidence: 99%